Efeect of the demulsifier additive on the performance characteristics of fuel oil - E. R. Zvereva; R. V. Khabibullina; E. S. Dremicheva; G. R. Akhmetvalieva; D. R. Gafiyatova (Известия высших учебных заведений: Проблемы энергетики)
Experimental studies of the effects of additive based on demulsifier diproksamin-157 on the performance characteristics of the fuel oil: the viscosity, pour point and the degree of dehydration at different temperatures and additive concentrations have been presented.